Why do preconception and pregnancy lifestyle interventions demonstrate limited success in preventing overweight and obesity in children? A scoping review protocol. - Kaat Philippe; Carla Perrotta; Aisling O'Donnell; Fionnuala M McAuliffe; Catherine M Phillips (PLoS ONE)
Adverse family-based lifestyle factors in the preconception period, pregnancy and early-childhood are major risk factors for childhood obesity and there is a growing consensus that early life interventions to prevent overweight and obesity in children are required. However, results from recent systematic reviews of preconception and pregnancy interventions have demonstrated mixed success. Therefore, this protocol presents a study aiming to summarise and evaluate complex preconception and pregnancy intervention components, process evaluation components, and authors' statements, with a view to improving our understanding regarding their success and informing design or adaptation of more effective interventions to prevent childhood obesity. A scoping review will be conducted, using the frameworks of the JBI and Arksey and O'Malley. A two-step approach will be used to identify relevant literature: (1) systematic searches will be conducted in the databases PubMed, Embase and CENTRAL to identify all eligible preconception and pregnancy trials with offspring data; and (2) CLUSTER searches will be conducted to find linked publications to eligible trials (follow-ups, process evaluation publications). Two researchers will independently select studies, chart, and synthesise data. A qualitative thematic analysis will be performed in which statements related to process evaluation components and authors' interpretations will be coded as "reasons". A descriptive analysis will be performed to evaluate intervention complexity using a complex intervention framework (AHRQ series; Medical Research Council guidance). The results of this study, which will be discussed with an expert group as part of a consultation stage, aim to identify gaps and inform the design or adaptation of future preconception and pregnancy interventions and approaches to potentially increase success rates. We expect that our results, which will be submitted for publication in a peer-reviewed journal, will be of interest to researchers, families, and practitioners concerned with good preconception and prenatal care, and healthy child outcomes.